“Kinabalu Ice Clasp”: A Case Report on Composite Recycled Bone Graft as a Support for Bone Graft Vascularization – Reimplantation of Campanacci Grade III GCT in the Distal Tibia. - Eyrique Goh Boay Heong (Universitas Nusa Cendana, 2026)
Giant cell tumour (GCT) of bone is an aggressive benign bone lesion. The tumour's juxta-articular location made treatment challenging, especially in Campanacci grade III. We present a case of a patient with Campanacci grade III GCT distal tibia who has undergone limb salvage surgery using “Kinabalu Ice Clasp” technique. A 23-year-old lady presented with a 6-month history of right ankle swelling. The ankle swelling has gradually increased in size and causing intermittent pain. Radiographs and MRI investigation showed an expansile osteolytic bone lesion with soft tissue extension at the metaphysis of the distal right tibia. The biopsy results confirmed the presence of Giant Cell Tumor (GCT) of bone. Four doses of Denosumab were administered before surgery to consolidate the tumour and assist with excision later. Subsequently patient underwent en bloc resection of the distal tibia. The defect was reconstructed using nitrogen treated of the diseased bone which was then used to encase the transposed vascularized fibular graft. Reconstruction in Campanacci III lesion with vascularized fibular, fortified with recycled bone graft is an efficient option to enhance protection of the underlying vascularized fibular graft while also serving as an extra scaffold for new bone incorporation.